1999
DOI: 10.1002/(sici)1097-0215(19991222)84:6<553::aid-ijc2>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Favorable clinical outcome of cervical cancers infected with human papilloma virus type 58 and related types

Abstract: To determine whether the status of human-papillomavirus (HPV) infection affects the clinical outcome of cervical carcinoma (CC), HPV genotype was prospectively determined in 94 consecutive CC cases subsequently followed for a median duration of 37.5 months. With a consensus PCR-RFLP method of HPV genotyping, 81 (86.2%) cancers were positive for HPV DNA. They were classified, according to the phylogenic similarities, into HPV-16-related (type 16, n ‫؍‬ 45; type 31, n ‫؍‬ 2), HPV-58-related (type 58, n ‫؍‬ 17; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
2
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 3 publications
1
46
2
1
Order By: Relevance
“…[5][6][7][8] A recent study found improved survival in patients with HPV 58 positive tumors. 33 The impact of multiple HPV infection, however, was not investigated. The incidence of multiple HPV infection varies and is related to the method of HPV detection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[5][6][7][8] A recent study found improved survival in patients with HPV 58 positive tumors. 33 The impact of multiple HPV infection, however, was not investigated. The incidence of multiple HPV infection varies and is related to the method of HPV detection.…”
Section: Discussionmentioning
confidence: 99%
“…32 Biotin-labeled, type specific double-stranded DNA probes for general screening (HPV 6,11,16,18,30,31,33,45, 51, 52) and type-specific probes against HPV 16, 18, 31 and 33 were used. This signal-amplified ISH method is considered to be highly specific and very sensitive for detection of HPV-DNA in tissue sections.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The remainder is due to other HPV types depending on geographical variations and ethnicity of the population (Smith et al, 2007). For example in Asian populations, HPV genotypes 52 and 58 are usually found while they are rare in Western countries (Lai et al, 1999). HPV typing provides important data for the distinction between high and low risk.…”
Section: Introductionmentioning
confidence: 99%